The “Bofills båge” in Stockholm. Nordic Peculiarities of a Postmodern Crescent - Bellucci, Giovanni (Histories of Postwar Architecture, 2024)
The facts about the redevelopment of the area formerly occupied by the railway tracks and the train station in the centre of the island of Södermalm in Stockholm began in 1981 with the competition for a new residential area. From the 125 projects evaluated by the jury, no winner was found, so the “Project group” coordinated by architect Jan Inghe-Hagström, who led the Stockholm City Planning Department at the time, implemented the best ideas in the final master plan Områdseplan84 (Area Plan84). The large area was subdivided into 14 districts entrusted to cooperatives and construction companies, including HSB, which was assigned the area to which a crescent was to be built and included a park. La selezione del progettista da parte di HSB avvenne dopo un nuovo concorso a inviti in cui Ricardo Bofill risultò vincitore all’inizio del 1985. Fino al 1987, i dettagli esecutivi del progetto sono stati studiati in un processo iterativo che ha coinvolto i progettisti di Taller, l’architetto Inghe-Hagström e l’appaltatore Ohlsson & Skarne. The start of construction in 1989 was followed by two years of building work, which resulted in Stockholm’s first crescent characterised by an extremely reduced decorative apparatus compared to Bofill’s similar residential complexes in France in particular. The demands of the client and the construction company, in view of the Nordic context historically reluctant to insert redundant decorative devices, led Bofill to make a number of changes to the first version of the project, leading to the final solution inaugurated in 1992. Although the subject of conflicting assessments, the ‘Bofill båge’ is today one of Stockholm’s most emblematic and recognisable architectures, where it stands out for its elegance and essentiality, combining traits of classical architectural language and tradition with the functional requirements of the north.